Development of a novel telomerase assay using the PPDK–luciferin–luciferase detection system. (2nd April 2013) - Karasawa, K.; Sano, Y.; Arakawa, H.
ABSTRACT Telomerase participates in malignant transformation or immortalization of cells, and has attracted attention as an anticancer drug screening and diagnostic tumor marker. We developed a novel telomerase assay called the PPDK–luciferin–luciferase system bioluminescence assay (PLLBA) using pyruvate phosphate dikinase (PPDK). In this assay, pyrophosphate produced by the telomerase reaction and polymerase chain reaction (PCR) is converted to ATP by PPDK, and ATP is detected by the firefly luciferin–luciferase reaction. In this work, telomerase substrate was obtained in accordance with the telomeric repeat amplification protocol (TRAP). Telomerase‐positive (500 cells/assay), ‐inactive (heated for 10 min at 85 °C) and ‐negative (only Chaps lysis buffer) samples were used. As a result, the findings clearly showed that the signal‐to‐noise (S/N) ratio of the positive cells was 39.5. After the telomerase reaction and PCR, PLLBA was completed 120 s later. A high level of reproducibility was obtained with ‐ coefficient of variation (CV) of 4.1% (positive cells). The detection limit for cells using telomerase was one cell per assay. This assay for telomerase activity was also shown to be adaptable to human cancer‐derived cell lines. Copyright © 2013 John Wiley & Sons, Ltd.